Jesus: A Revolutionary Biography, by John Dominic Crossan and Meeting Jesus Again for the First Time: The Historical Jesus & The Heart of Contemporary Faith, by Marcus J. Borg - Sinacore-Guinn, David (Arc: The Journal of the School of Religious Studies, 1995)
The author in this one submission offers a review of two different books, which seek to discuss the historical Jesus. 1. Jesus: A Revolutionary Biography. By John Dominic Crossan. San Francisco: Harper San Francisco, 1994. ISBN 0-061669-5. Pp. xiv+209. 2. Meeting Jesus Again for the First Time: The Historical Jesus & The Heart of Contemporary Faith. By Marcus J. Borg. San Francisco: Harper San Francisco, 1994. ISBN 0-06-060916-8. Pp. ix+150.